The effect of patient-centered communication on medication intake: an experimental study. Issue 10 (26th November 2022) - Haas, Julia W; Rief, Winfried; Weiß, Frauke; Doering, Bettina K; Kleinstäuber, Maria; Ruwoldt, Sina; Sarter, Lena; Thomas, Ruth; Rheker, Julia
ABSTRACT: It is not only crucial to provide patients with information, but also to communicate this information in a way to enable patient participation in health decisions. Experimental studies investigating the association between the communication style of health professionals and patients' health decisions are rare, which limits causal conclusions. This study investigated the effect of a doctor's patient-centered communication style on the likelihood to take a medication. Healthy women (N = 120) were randomly allocated to one of three groups. They either received a medical consultation characterized by a patient-centered communication style (PC group) or by a doctor-centered communication style (DC group) or they received no consultation at all (control group). All participants were told that the study would investigate the effects of a 'concentration-enhancing medication'. Voluntary intake of the medication (a placebo pill) served as behavioral outcome. Participants' self-rated intention to take the medication was measured at three assessment points. Data were analyzed using a Chi-square-test and a mixed analysis of covariance. In each group, 40 participants were analyzed. Following the consultation, groups did not differ regarding the behavioral outcome, but participants' intention to take the medication was higher in the PC group compared with the control group. Our results indicate that patient-centered communication has a beneficial influence on participants' intention to take medication. Future studies should investigate the role of communication in individuals with health conditions that require a specified treatment plan and taking medication over the long-term.